Ecosystem Metabolisms and Functions: An eco-literacy framework and model for designers - Snow, Tom (FormAkademisk, 2020)
The framework and model describe ecosystem functions. Working within and towards systems of production that intend to be truly circular and regenerative necessitates that designers (and other stakeholders) have an increased understanding and intuition of how ecosystems function—an eco-literacy. To this end, the framework is based on foundational metabolisms (producers, consumers and decomposers), and their interactions with each other and ‘nutrient pools’ within their collective environment. The model proposes that ecosystems are fractals of plants and are one collective metabolism. Some ‘ecosystem concepts’ are also developed that can be worked with as they are or used as a base for analogies for those working directly with, or developing frameworks for, integrative systems of production. Keywords: Systemic design, ecological design, biomimetics, circular economy, systems ecology.